Our action gets multiplied (Journal of Parents and Teachers, 2017)
The students of 3º Grade of Primary Education from Universidad Pontificia Comillas have a mission: to collaborate with the Fundación del Valle in the formation of 60 teachers on the multiplication in Guatemala. For this, we have made manipulative materials, dynamics and games based on a theoretical foundation. This project has been very enriching at a professional and personal level, and although we were the artisans, the protagonists were always the children from Guatemala.
Keywords: learning service; multiplication; mathematics; materials and resources; education; emotions; Guatemala; problem-based teaching (ABP)